Tinjauan Pustaka : Kanker Pankreas - Nita Rahmi; Haris Hutagaol (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Pancreatic cancer is the seventh leading cause of cancer death globally according to Global Cancer Statistics 2020. Pancreatic cancer does not show clear clinical signs in the early stages and is usually diagnosed in the advanced stages with poor response to treatment. The risk is increased in smokers, black race, high-fat diet, alcohol, elderly, presence of infection, diabetes mellitus, and chronic pancreatitis. Histopathology is the gold standard for diagnosing pancreatic cancer. Better knowledge of risk factors, genetics, molecular pathogenesis, symptoms associated with this disease, and laboratory aspects is essential to inform health professionals and the general public for potential preventive and/or early detection measures.